The Effect of Leaves Sweet Potato Stew on Hemoglobin Levels in the Third Month of Pregnancy - Alfika Awatiszahro; Betanuari Sabda Nirwana (Universitas STRADA Indonesia, 2021)
Anemia is often experienced by pregnant women on average due to iron deficiency. Anemia can cause complications in pregnancy and childbirth. Provision of boiled sweet potato leaves containing vitamin C and iron is expected to be an alternative in increasing hemoglobin levels in pregnant women. This study aims to determine the effect of giving boiled water from sweet potato leaves to increase hemoglobin levels in third trimester pregnant women in the Gemarang Ngawi Health Center Work Area. Method. The research design used was a pre-experimental design with a pre-experimental design. The research sample was pregnant women in the third trimester in the Gemarang Ngawi Health Center working area, totaling 16 respondents. The data collection instrument used an Hb measuring device and an observation sheet. This study used a paired T test, a p value of 0.000 was obtained, which means that there was an effect of giving boiled water from sweet potato leaves to the Hb levels of pregnant women in the third trimester. Sweet Potato Leaf Boiled Water contains vitamin C and iron, where vitamin C helps iron absorption, while iron in Sweet Potato Leaf Boiled Water can help synthesize hemoglobin in third trimester pregnant women to reduce the incidence of anemia. Health workers should recommend that pregnant women consume boiled water of sweet potato leaves because it can be used as an alternative in overcoming anemia in third trimester pregnant women.